Higher NICU admissions in infants born at ≥35 weeks gestational age during the COVID-19 pandemic - Jegatheesan, Priya; Narasimhan, Sudha Rani; Huang, Angela; Nudelman, Matthew; Song, Dongli (Frontiers in Pediatrics, 2023)
Background: Increasing evidence has shown that the COVID-19 pandemic has had a profound negative impact on vulnerable populations and a significant effect on maternal and neonatal health. We observed an increase in the percentage of infants admitted to NICU from 8% to 10% in the first year of the pandemic. This study aimed to compare the delivery room outcomes, NICU admissions and interventions, and neonatal outcomes two years before and during the pandemic. Methods: This was a retrospective study in a public hospital between pre-COVID-19